Parenting Management in Improving Early Childhood Spirituality at Raudhatul Athfal Indramayu - Umyati Umyati; Abdus Salam; Ade Aspandi; Abdul Karim (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze the planning, implementation, evaluation, and challenges of parenting management in strengthening early childhood spirituality at Raudhatul Athfal institutions in Indramayu. Using a descriptive qualitative approach, data were collected through interviews with teachers and parents, observation of activities, and document analysis of academic programs. The findings show that parenting programs were systematically planned at the beginning of the academic year through work meetings involving school leaders, teachers, committees, and parents. Programs were implemented in two main forms: seminars addressing child development and spirituality, and joint activities such as outing classes, cooking classes, and manasik haji training that encouraged parent–child interaction. Evaluation was carried out during and after the activities through discussions, questionnaires, and internal meetings, providing feedback for program improvement. Despite these efforts, challenges remained, including limited parental attendance, inadequate facilities, and weak collaboration between schools and families. The results indicate that structured parenting management strengthens parents’ understanding and participation in fostering children’s spiritual development. This research concludes that effective collaboration between schools and parents through managed parenting programs plays a vital role in building children’s spiritual foundations, providing valuable insights for educators and policymakers in early childhood education.